EFFECTS OF INDIVIDUALLY CONSTRUCTED ORAL APPLIANCE ON THE POLYSOMNOGRAPHIC PARAMETERS IN PATIENTS WITH OBSTRUCTIVE SLEEP APNEA - Lyubomir Grozev; Kiril Terziyski; Aneliya Draganova; Iliyan Hristov (Peytchinski Publishing, 2018)
Background: Obstructive sleep apnea (OSA) is a common sleep disorder, associated with disturbed noxturnal oxygenation profile and altered sleep structure, associated with significant health problems. Oral appliances (OA) are used as an alternative therapeutic option for patients with mild to moderate OSA. Although the application of OA does not always result in a complete resolution of the sleep-disordered breathing, greater patient adherence is demonstrated. We have decided to evaluate the effect of individually constructed OA on sleep-disordered breathing and sleep structure in patients with OSA. Materials and methods: 20 patients (18 men) with OSA (age 46.3±8.1 years (mean±SD), body mass index 29.0±4.8 kg.m-2) were subjected to a full-night polysomnography (PSG), at baseline and one month after the introduction of an OA. Results: A significant decrease in AHI (33.4±31.1 vs 45.5±30.8, p<0.001), hypopnea index (10.3±9.1 vs 18.2±11.0, p=0.023), mean duration of apneas (20.9±6.9 vs 24.1±6.4 sec, p=0.005) and average desaturation (5.6±2.4 vs 8.5±3.0 %, p<0.001), after therapy and at baseline, respectively, was registered. Sleep structure was improved as indicated by an increase in REM (16.1±6.2vs 12.3±8.2 % of total sleep time, p=0.016) and a decrease in arousal index (31.0±14.2 vs 46.4±12.0, p<0.001). Conclusion: OA is a reasonable alternative for the treatment of patients with moderate and severe OSA, resulting in an improvement of the polysomnographic parameters and expressed by excellent patient compliance.